Value management implementation in construction a global view - Oke, Ayodeji Emmanuel; Stephen, Seyi S.; Aigbavboa, Clinton (Emerald Publishing, 2022)
Value Management Implementation in Constructionaddresses various factors that can enhance the application of the discipline as well as its adoption among concerned stakeholders and discusses the practice of value management in various developed and developing countries
Keywords: Value analysis (Cost control); Construction industry / Management; Analyse de la valeur; Construction / Industrie / Gestion; Electronic books